Magnetically separable Ag3PO4/NiFe2O4 composites with enhanced photocatalytic activity. Issue 47 (28th October 2015) - Patil, Santosh S.; Tamboli, Mohaseen S.; Deonikar, Virendrakumar G.; Umarji, Govind G.; Ambekar, Jalindar D.; Kulkarni, Milind V.; Kolekar, Sanjay S.; Kale, Bharat B.; Patil, Deepak R.
Abstract : A step wise growth process of APO nuclei leads to developing interesting morphologies of APO/NFO composites. Abstract : Magnetically separable Ag3 PO4 /NiFe2 O4 (APO/NFO) composites were prepared by an in situ precipitation method. The photocatalytic activity of photocatalysts consisting of different APO/NFO mass ratios was evaluated by degradation of methylene blue (MB) under visible light irradiation. The excellent photocatalytic activity was observed using APO/NFO5 (5% NFO) composites with good cycling stability which is higher than that of pure Ag3 PO4 and NiFe2 O4 . All the APO/NFO composites showed good magnetic behavior, which makes them magnetically separable after reaction and reusable for several experiments. Photoconductivities of pure and composite samples were examined to study the photoresponse characteristics. The current intensity greatly enhanced by loading NFO to APO. Furthermore, the photocatalytic performance of the samples is correlated with the conductivity of the samples. The enhancement in the photocatalytic activity of APO/NFO composites for MB degradation is attributed to the excellent conductivity of APO/NFO composites through the co-catalytic effect of NFO by providing accelerated charge separation through the n–n interface.